USING PISA 2003, EXAMINING THE FACTORS AFFECTING STUDENTS' MATHEMATICS ACHIEVEMENT - Demir, Ibrahim; Kilic, Serpil (HACETTEPE UNIV, 2010)
The purpose of this study is to examine the effects of learning strategies on mathematics achievement. The sample was compiled from students who participated in Programme for International Student Assessment (PISA) in Turkey. The data consisted of 4493 15 years old Turkish students in 158 schools, and analyzed by two levels Bernoulli model as a special case of hierarchical generalized linear models. These clustered data set with a two level hierarchical structure examined students nested within different schools. Two levels Bernoulli model was used to estimate coefficients and modeled differences across schools. Results from this study indicate that school location, gender and interest in and enjoyment of mathematics variables had positive effects, and elaboration learning strategies variable had strong negative effects on mathematics achievement.
Keywords: hierarchical generalized linear model; learning strategies; mathematics achievement; pisa; two-level bernoulli model; REGRESSION-MODEL; THINKING; SCIENCE; Education & Educational Research